Evocations about Carlos Forcadell - Fernández Clemente, Eloy (Huarte de San Juan. Geografía e Historia, 2016)
The author (after organising hundreds of notes, revising exhaustive reports and many common publications) is surprised by something he had not noticed with that much intensity: the extraordinary parallelism that-with three and a half years less tan Carlos Forcadell (emeritus professor of Contemporary History in Zaragoza) and some minor professional and ideological divergences, has accompanied them in the last half century. With this study, he goes along with the tributes that come and will come when he retires and he affirms that he is one of his more permanent and greatest friends and also that he is a very distinguished historian. However, other people will be talking about all of these on the occasion of his emeritus professor position. Neither he talks about careers, investigation projects, thesis, courts, etc. in which he has been an tireless worker.